Finkelstein's Test Is Superior to Eichhoff's Test in the Investigation of de Quervain's Disease - Wu, Feiran; Rajpura, Asim; Sandher, Dilraj (Journal of Hand and Microsurgery, 2018)
Introduction de Quervain's tenosynovitis is a common pathologic condition of the hand. Finkelstein's test has long been considered to be a pathognomonic sign of this diagnosis, yet most clinicians and instruction manuals erroneously describe what is in fact the Eichhoff's test, which is thought to produce similar pain by tendon stretching in a normal wrist. The purpose of this study was to compare Finkelstein's test with Eichhoff's test in asymptomatic individuals.Materials and Methods Thirty-six asymptomatic participants (72 wrists) were examined using both Finkelstein's and Eichhoff's tests with a minimum interval of 24 hours between the tests.Results The results showed that Finkelstein's test was more accurate than Eichhoff's test. It demonstrated higher specificity, produced significantly fewer numbers of false-positive results, and also caused significantly less discomfort to patients.Conclusion This study recommends Finkelstein's test as the clinical examination of choice for the diagnosis of de Quervain's disease.
Keywords: de Quervain's disease; Eichhoff's test; false-positive result; Finkelstein's test